Possibilidades didáticas com Educação Financeira Escolar Crítica nos anos iniciais do Ensino Fundamental - Faria, Wilma Pereira Santos (2020)
This research presents a reflection and analysis on a didactic proposal developed with students of the 5th year of Elementary Education in a federal public school - Colégio de Aplicação, Universidade Federal de Uberlândia. In this scenario, we organized moments called Workshop to know, present and explore situations that encourage debate and reflection on financial issues such as decision making, money and happiness, need and desire, control of expenses and expenses, budget , planning and dialogue as an exchange of experiences and perspectives. The objective of this research is to investigate the possibilities of critical reflections in the face of the financial context, taking into account the reality of the students and the dynamics of the meetings provided in the classroom. The research aims to answers to the following question: What contributions to citizen education could be viable from teaching proposals that approach Financial Education in a class of 5th year of Elementary Education in a critical, conscious and reflective way? Dialoging with authors who study FE and mainly School Financial Education (EFE) from Skovsmose (2000) Critical Mathematical Education (CME) learning environments, a qualitative analysis of the material produced during the Workshop meetings and also before and after the moments. The main results of this study indicate that it is possible to enhance characteristics such as criticality, reflection and investigation with tasks in the classroom addressing FE since the early years. The Workshop provided students and the teacher with opportunities for dialogues that valued personal perspectives and experiences and the possibilities for improving opinions. As it is a Professional Master's program, it was decided to elaborate the educational product in booklet format, providing support material for teacher and student.